The effect of an adapted training protocol on ankle joint mobility in young soccer players - Francia, P.; Marini, C. F.; Toni, S.; Mencarelli, A.; Iannone, G.; Lucertini, F.; Brandoni, G.; Monteiro-Soares, M.; Federici, A.; Piccini, B. (Medicina dello Sport, 2020)
BACKGROUND: Soccer practice can induce marked changes in ankle joint mobility (AJM) with dreaded consequences. The aim of this study was to evaluate the effects of an adapted training protocol (TP) on the AJM of young soccer players. METHODS: In 31 male soccer players (age 13.2±0.5 years) and in 31 volleyball players matched for age, sex, and Body Mass Index, AJM was evaluated by using an inclinometer while the inclination of the leg on the sagittal plane was assessed by analysis of images. Soccer players performed two months (10 sessions) of a TP that included 4 exercises aimed at improving AJM. RESULTS: At baseline, soccer players showed reduced AJM compared to volleyball players (127.6±15.3° vs. 141.0±20.5°; P<0.01) and a minor angle between leg and foot when evaluated in lying position (294.4±13.2° vs. 304.3±9.8°; P<0.001). TP produced a significant positive effect on ankle range of motion (ROM) in plantar flexion (P<0.001) but not in dorsiflexion. The limb of measurement (dominant-nondominant) did not affect AJM. The foot posture of subjects in lying supine was in dorsiflexion compared to controls (P<0.001). CONCLUSIONS: Young soccer players showed a significant reduction in AJM, which was difficult to recover, even following a TP. These results indicate that further studies in this field are needed.